Limitations for healthy container traffic on the Swedish inland waterways - Possible conversion to container shipping within Lake Vänern - Colldén, Ronja; Djerf, Viktor (My University, 2023)
In Sweden, most cargo is transported by trucks on the roads. This leads to congestion and high greenhouse gas emissions in relation to the amount of transported goods. The Swedish inland water ways (IWW) have capacity to take on goods from the roads to ease the congestions and decrease the greenhouse gas emissions. Today, it is almost exclusively bulk cargo that is being transported in the Swedish IWW. This study was performed in lake Vänern in Sweden and aim to investigate the technical hinders for an efficient container trade between the ports in lake Vänern and Gothenburg. The methods used in this study were a combination of literature studies and interview. The results show that for a container trade through lake Vänern to be possible, the port would need to invest in more powerful cranes as well as recondition the quay to support the increased weight. The investigation further shows that issues such as the lock rebuilding in Trollhättan and pilot shortage pose as a larger obstacle to IWW traffic with container cargo.
Keywords: Inland waterways; Container shipping; Lake Vänern; Transport